Addition to the checklist of spiders (Araneae) of Kharkiv Region (Ukraine) - Полчанінова, Н. Ю.; Слуцький, О. І. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
A list of 206 spider species from 48 localities of Kharkiv Region is given. One species, Emblyna brevidens, is the first record for Ukraine, 22 species are new for Kharkiv Region. 30-year old finds have been confirmed for two species; three species are reinstituted in the list but previous records remain erroneous. All species are provided with the data regarding new collecting localities within the region.